Comparison of Indoor vs Outdoor Induction of Labour in Full Term Uncomplicated Pregnancies. - Uzma Almas, Zainab Maqsood, Rubina Qadir, Majida Zafar, Nasira Tasneem, Khawar Sultan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Induction of labour is an obstetric intervention when the continuation of pregnancy seems to be less beneficial than delivery. Cervical ripening increases the rate of success of labour and normal vaginal delivery. Outpatient cervical ripening is a striking option with benefits of increase maternal satisfaction, reduce hospital stay workload on health care resources Aim: To compare the fetomaternal outcome of indoor vs outdoor induction Methods: An observational cross sectional study was conducted in MCH PIMS, after taking approval from ethical review board from July 1, 2019 to December 31, 2019. A total of 412 women with singleton pregnancy of cephalic presentation and full term gestation were included. Group A was retained in emergency after induction (outdoor patient) while group B (indoor patient) induction was done in ward. All women followed till delivery and fetomaternal outcome i.e. cesarean section, apgar score <7 at 5 minutes, meconium aspiration syndrome and NICU admission (yes/no) were noted. Results: In this study, caesarean section was recorded in 44(21.36%) patients with outdoor induction while in 67(32.52%) in women with indoor induction, Apgar score <7 at 5 minutes was recorded in 4(1.94%) vs 15(7.28%) respectively, meconium aspiration syndrome in 6(2.91%) vs 35(16.99%) respectively and NICU admission in 3 (1.46%) versus 23(11.17%) respectively Conclusion: This study concluded that outdoor induction is better in terms of fetomaternal outcome as compared to indoor induction. Keywords: Induction of labour, outdoor, cesarean section.